2020
DOI: 10.23939/mmc2020.01.029
|View full text |Cite
|
Sign up to set email alerts
|

The method of inverse problems of dynamics for the synthesis of a system of stabilization of the movement of a dynamic object on operatively programmable trajectories

Abstract: The article is devoted to the analysis of the possibility of applying the method of inverse problems of dynamics for the synthesis of a system of spatial stabilization of the motion of a dynamic object on an operatively programmable trajectory. The article proposes to apply the method of inverse problems of dynamics for the synthesis of a system for stabilizing the motion of a dynamic object on an operatively programmable trajectory. It is concluded that the procedure for applying the method of inverse problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…The concept of ensuring the functional stability of an organizational system can be applied to a wide variety of systems [12]. This can be a military unit, a business organization, or some complex mechanism, such as an entire country's IT infrastructure or energy infrastructure.…”
Section: Methodsmentioning
confidence: 99%
“…The concept of ensuring the functional stability of an organizational system can be applied to a wide variety of systems [12]. This can be a military unit, a business organization, or some complex mechanism, such as an entire country's IT infrastructure or energy infrastructure.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis of models and methods forprediction ofaircraft motion, which are implemented nowadays, showed that this problem is solved within the framework of fixed ideas about the nature of aircraft motion [25][26][27][28]. However, it should be noted that the modern aircraft have high maneuverability; accordingly, the motion can occur in critical situations and the physical trajectory of motion may not be taken be into account.…”
Section: Numerical Experimentsmentioning
confidence: 99%